2018
DOI: 10.1186/s40816-018-0081-z
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and pharmacological evaluation of methanolic extract of Lathyrus sativus L. seeds

Abstract: Background: Lathyrus sativus L. (Fabaceae) has long been used as a traditional medicine for the treatment of several ailments such as Scabies, eczema, and allergy. The aim of the study was to evaluate the phytochemical nature with Central Nervous System (CNS) depressant, analgesic, antipyretic activities of the methanolic plant extract of Lathyrus sativus L. seeds in different experimental models. Methods: Preliminary phytochemical screening and proximate analysis was carried out using different standard metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Recently, Bhattacharjee et al evaluated the analgesic activity of methanolic extract of Lathyrus sativus seeds at the dose 200 and 300 mg/kg b. wt. and found a very significant inhibition (87.09% and 80.65%) of writhes induced by acetic acid in mice in comparison to indomethacin (70.97%) [44]. Consequently, a similar kind of the finding was made by the Islam et al with extract of Campsis radicans, where he took the doses of 200 and 400 mg/kg b.wt., and proved high analgesic activity [45].…”
Section: Discussionmentioning
confidence: 58%
“…Recently, Bhattacharjee et al evaluated the analgesic activity of methanolic extract of Lathyrus sativus seeds at the dose 200 and 300 mg/kg b. wt. and found a very significant inhibition (87.09% and 80.65%) of writhes induced by acetic acid in mice in comparison to indomethacin (70.97%) [44]. Consequently, a similar kind of the finding was made by the Islam et al with extract of Campsis radicans, where he took the doses of 200 and 400 mg/kg b.wt., and proved high analgesic activity [45].…”
Section: Discussionmentioning
confidence: 58%
“…This study evaluated the hypoglycemic and in vitro antioxidant activities of SKSB extract. The extract contained diverse constituents, including saponins, terpenes, tannins, steroids, flavonoids, carbohydrates and alkaloids, an indication of the richness of the plant in phytochemicals that may have bioactive properties (Bhattacharjee et al, 2018). It has been reported that the common phytoconstituents found in medicinal plants with anti-diabetic potential include polyphenols, flavonoids, terpenoids, tannins, alkaloids, saponins (Mohd et al, 2017).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…Lathyrus sativus is a well-known plant that contains alkaloids, carotenoids, flavonoids, starch, carbohydrates, essential oil, leguminvicilin, legumelin, vitamin C, oleoresin, gum resin, tannins, terpenes, phenols, riboflavin, beta-carotene, proteins, and amino acids, which act as capping, reducing and stabilizing agents [17,18]. Thanks to this unique feature, many research groups have used L. sativus shell extract to synthesize magnetite nanoparticles [19,20].…”
Section: Green Synthesis Of Hybrid Magnetic-semiconductor Oxides Nano...mentioning
confidence: 99%